(untitled) (International Journal of Engineering and Computer Science, 2017)
Big Data in Healthcare refers to handling the large and complex sets of data and making it accessible at finger tips. Earlier, the data in healthcare used to reach a level of complexity from where it used to become next to impossible to extract that data and bring it to use. This leads to slow growth in healthcare industry. Big Data becomes much more interesting when it is used in healthcare analytics. The other potential benefits that big data provides is the detection (Analysis) of diseases beforehand which allows doctors to act treat proactively. This will also help in detecting fraud in healthcare more quickly and efficiently, By bringing into use of statistical tools and algorithms, there could be a faster development of more accurately targeted vaccines. The tools are used to help developing the cost effective ways for discovering more clinically relevant ways to analyse the disease and treat the patients in an effective manner. The objective of this paper analyzes importance of big data and the various steps involved in machine learning techniques in healthcare. This paper also identifies the big data analytics are helping to realize the goals of diagnosing, treating, helping, and healing all patients in need of healthcare.